Anatomical evidence links the stomach to the central amygdala, a region responsive to local GLP-1R agonist induced feeding and nausea-like behaviors in male mice - Yang, Hui; Yu, Wenxiang; Gao, Yunling; Wang, Jie; Xu, Shaoyong (Frontiers in Endocrinology, 2026)
BackgroundThe glucagon-like peptide-1 receptor (GLP-1R) agonist liraglutide is an effective therapeutic agent for obesity, primarily through its ability to suppress appetite and delay gastric emptying. However, the central neural substrates mediating its effects on food intake remain incompletely defined.MethodsMale mice received subcutaneous liraglutide injections in the cervical region to evalutates its effects on feeding behavior and body weight regulation. Retrograde transsynaptic tracing using pseudorabies virus (PRV) was employed to identify central amygdala (CeA) involvement in gastric-related neural circuits. The functional role of the CeA in feeding regulation was examined using chemogenetic and optogenetic activation, while local microinjection of GLP-1R agonists or antagonists into the CeA was used to evaluate receptor-specific effects.ResultsGastric wall injection of PRV anatomically revealed a direct connection between the stomach and the CeA. Site-specific administration of GLP-1R agonists into the CeA induced hypophagia and nausea-like behaviors in male mice.ConclusionsThis study provides anatomical evidence that the CeA of male mice is involved in gastric regulatory circuits, and shows that the CeA responds to site-specific GLP-1R activation to induce hypophagia and nausea-like behaviors.